THE ROLE OF SERVICE EMPLOYEES IN CULTURAL CAPITAL ENHANCEMENT WITHIN A THEMATIC DESSERT BAR IN NORTH JAKARTA - Kevin Gustian Yulius; Tiffany Wu (Journal of Business And Entrepreneurship, 2026)
The growing trend of thematic food and beverage establishments highlights a shift toward experience-driven consumption; however, limited attention has been given to how service employees contribute to the creation of cultural value within such settings. This study aims to examine the role of service employees in enhancing cultural capital within a thematic dessert bar context, using Zoé Dessert Bar in North Jakarta as a case study. A descriptive exploratory approach was employed using survey data collected from 352 respondents through purposive sampling. The findings indicate that customer preferences are strongly influenced by experiential elements such as ambiance, uniqueness, and narrative-based service. More importantly, service employees play a central role as cultural intermediaries who translate thematic concepts into meaningful interactions, facilitating customers’ engagement with symbolic and cultural value. This study contributes to the literature by demonstrating that cultural capital is not only an outcome of consumption but is actively co-created through employee–customer interactions. The findings also highlight the importance of human resource strategies that emphasize storytelling ability, cultural literacy, and interpersonal skills in delivering thematic service experiences.